Morphological analyses of two gynandromorphy individuals of Geometridae (Lepidoptera: Geometridae) - S. Seven; M. Özdemir (SHILAP, 2024)
In this study, gynandromorphs individuals of Gnopharmia cholcidaria (Lederer, 1870) and Idea adeversaria (Linnaeus, 1758) from Turkey were observed morphologically, compared to each other and normal individuals. Idea adevarsaria shows female characteristics in external morphology. Howewer, Gnopharmia colchidaria shows both male and female characteristics in phenotype, which has external characters of female on the left and of male on the right side. Though male genitalia is dominant in G. colchidaria, characteristics concerning both male and female genitalia are found to be equal in I. devarsaria. Morphological structures and their measurements in gynandromorph individuals are given and figured.